Factors Related to Adolescent Smoking: A Nationally Representative Cross-Sectional Study in Thailand - Suwanwong, Charin; Kalapat, Romtawan; Pitayarangsarit, Siriwan; Chaiyasong, Surasak (Open Access Macedonian Journal of Medical Sciences, 2021)
Objective: This study aimed to explore the individual, familial, and social factors associated with different smoking status in Thai adolescents from the 2017 Cigarette Smoking and Alcohol Drinking Behavior Survey (CSAD) Methods: The nationally representative sample of 6046 adolescents aged 15-19 years who took part in the 2017 CSAD in Thailand. Multinomial logistic regression analysis was conducted to explore the associations between the individual, familial, and social factors and different smoking status. Results: The daily smoking and occasional smoking was 6.4% and 3.3%, respectively. Gender, alcohol use, substance use, attitudes toward smoking, exposure to secondhand smoke at home, anti-smoking social media campaign, and graphic warning labels were related to both daily and occasional smoking. Daily smoking was associated with exposure to secondhand smoke at school, restaurant, and public transport, and exposure to tobacco advertising. Conclusion: These findings suggest that smoking prevention intervention should particularly focus on these factors and also need to develop the anti-smoking policies for smoking prevention among adolescents.